ANTIBACTERIAL POTENTIAL OF DAYAK ONION BULB EXTRACT (Eleutherine sp) AS A TREATMENT FOR ACNE VULGARIS: A LITERATURE REVIEW - Pradhea, Tifani Antonia; Clarissa, Maria; Ridho, Muhammad; Aqsa, Sadilla; Sumarna, Dimas Aldianakhi; Assegaf, Syarifah Nurul Yanti Syahab; Zakiah, Mistika (Medika Kartika : Jurnal Kedokteran dan Kesehatan, 2025)
Acne vulgaris is a common skin disorder that can significantly affect quality of life. Although conventional antibiotic treatments are commonly used, herbal alternatives such as Eleutherine sp. (Dayak onion) bulb extract may offer therapeutic options for acne vulgaris. This study is a literature review that evaluates the antibacterial activity of Dayak onion bulb extract against bacteria that cause acne vulgaris. The search was conducted in the ScienceDirect, PubMed, Google Scholar, and Garuda databases, focusing on in vitro studies published in the last 10 years. Of the 8 articles analyzed, Dayak onion bulb extract was effective against Staphylococcus aureus, Staphylococcus epidermidis, and Propionibacterium acnes. The best antibacterial activity was obtained from extracts at high concentrations with several methods. Temperature and incubation duration also affected the results. Active compounds such as flavonoids, alkaloids, triterpenoids, steroids, and tannins contributed to the antibacterial effectiveness of this extract. Dayak onion bulb extract showed strong antibacterial effectiveness, making it a potential alternative for treating acne vulgaris. This extract as an additional therapy offers a safe option as a natural acne vulgaris treatment solution. Keywords: acne vulgaris, antibacterial, Eleutherine DOI : 10.35990/mk.v8n4.p446-457